Knowledge and action - Meusburger, Peter; Werlen, Benno; Kaeding-Suarsana, Laura (Knowledge and space, 2017)
This book is open access under a CC BY 4.0 license. This volume explores interdependencies between knowledge, action, and space from different interdisciplinary perspectives. Some of the contributors discuss knowledge as a social construct based on collective action, while others look at knowledge as an individual capacity for action. The chapters contain theoretical frameworks as well as experimental outcomes. Readers will gain insight into key questions such as: How does knowledge function as a prerequisite for action? Why are knowledge gaps growing and not diminishing in a knowledge society? How much knowledge is necessary for action? How do various types of knowledge influence the steps from cognition to action? How do different representations of knowledge shape action? What impact have spatial conditions for the formation of knowledge? What is the relationship between social and geographical space? The contributors consider rationality in social and economic theories as well as in everyday life. Attention is also given to action theoretic approaches and rationality from the viewpoints of psychology, post-structuralism, and human geography, making this an attractive book for students, researchers and academics of various backgrounds
Keywords: Konferenzschrift